Anticipating demand shocks: Patient capital and the supply of housing. (January 2023) - Brill, Frances; Raco, Mike; Ward, Callum
'Patient capital' is presented by many policymakers as a panacea to address domestic (and sometimes city-level) gaps in financing urban development, particularly housing, that emerged in the post-2008 credit crunch. In this article, we analyse the complexities of patient investors' entry into residential markets in London and their response to the first major, and unexpected, crisis of demand: the COVID-19 pandemic and immediate falls in market demand. We focus on how patient capital and the firms invested in the professionalised rental market, build to rent (BTR), have responded. We highlight three main responses: (1) advancing their lobbying efforts to secure a more supportive political environment; (2) protecting their income streams by offering new payment plans and adaptability to prevent void rates; (3) turning to a 'reserve army' of renters backed by the state – so-called Key Workers (KWs). We argue these demonstrate a continual and co-evolutionary dimension to policy promoting patient capital and the need for patient planning to govern patient investment in housing systems. Our findings are in 'real-time' and highlight the importance of structural uncertainties and the breakdown of long-term assumptions in shaping investment decisions.